Head Circumference of Babies at Birth in Nigeria - Pam, Victor Chung (J Trop Pediatr, 2019)
BACKGROUND AND OBJECTIVES: Measuring head circumference (HC) of newborns is an important tool for evaluating intra-uterine brain development. HC reference charts currently in use in Nigeria are not representative of the local population. We thus present locally derived HC reference data for Nigerian infants at birth. SUBJECTS AND METHODS: We reviewed birth records of all infants at the Jos University Teaching Hospital (JUTH) over a 10 year period from January 2006. JUTH is a tertiary care center offering obstetric services to a large population of women in Jos and its environs. All births with gestational age between 28 and 42 weeks were included in the study. STATA version 14 was used to calculate gestational age associated HC percentile measurements. RESULTS: We included 18 282 babies to generate the reference values. The mean HC value was 34.4 ± 2.1 cm (M = 34.6 ± 2.16 cm, F = 34.1 ± 2.02 cm, p < 0.001). Our HC reference values significantly differ from the USA and INTERGROWTH-21 charts currently in use in our country. Mean HC was higher in male infants compared with female infants. This difference was uniformly so across all gestational age groups. CONCLUSIONS: The use of our locally derived HC reference values could be more appropriate in defining normal head growth in Nigerian infant populations thereby improving newborn care.